Diversidade taxonômica e potencial enzimático microbiano de solos de cavernas ferríferas do Parque Nacional dos Campos Ferruginosos, Serra de Carajás-PA, Brasil - Lima, Brenda Almeida (2023)
The caves hosted in iron ore are unique and extreme habitats, which are home to a great diversity of microorganisms that are still little known. Thus, studies on the taxonomic, functional diversity and biotechnological potential are of paramount importance to expand knowledge about the microbiota associated with the iron caves of Carajás. The objective of this study was to prospect the cultivable microbiota in order to identify the microbial diversity and the enzymatic potential associated with the bacterial strains and to characterize the soils regarding the physical and chemical aspects of iron caves in the Parque Nacional dos Campos Ferruginosos, in the state of Pará, Brazil . Soil samples were collected from the surface layer of caves GEM-1423 and GEM-1462 at three points in different zones (photic, penumbra and aphotic). The sampled soils were characterized in terms of granular and textural structure. The determination of total metal contents was performed by nitro-perchloric digestion and quantified in atomic absorption spectrometry. For selection of target bacteria, subsamples were diluted in sterile sodium chloride solution and incubated in an orbital shaker overnight for 24 hours. After the incubation period, the solutions were diluted from 10-2 to 10-3 and inoculated on the surface of the Luria Bertani medium (LB). For the identification of bacterial isolates, DNA was extracted and the 16S rDNA gene was sequenced using the Illumina platform. The functional analysis of the isolates was evaluated by cellulolytic, lipolytic, proteolytic, ureolytic activities, phosphate and potassium solubilization. All analyzes were performed in triplicate and statistically analyzed using the R software. The quantified metals were significant in the caves and affect enzymatic activity correlated with the main identified abundant genera. 29 bacterial strains were isolated, 18 bacteria from GEM-1423 cave and 11 bacteria from GEM-1462 cave. The main phyla identified were Actinobacteria, Firmicutes, Proteobacteria, Plactomycetes and Acidobacteria. The different domains of genera associated with the main phyla highlighted Bacillus, Blastopirellula, Lactobacillus, Serratia and a non-cultivable taxon as the most abundant in isolated bacterial strains. All bacteria showed enzymatic activity for two to five carbon sources tested and the enzymatic indices produced were significant. The results of this study will be useful for the management plan of the Campos Ferruginosos National Park, aiming to contribute to the conservation of the Carajás iron caves, and mainly to elucidate the systematics of bacterial communities and future biotechnological applications.